Edukasi Pembelajaran Matematika melalui Pendampingan Bimbingan Belajar untuk Meningkatkan Kemampuan Berhitung Siswa SD di Desa Kenari, Surabaya - Annisa Suci Maryana (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
The mathematics learning education program through learning assistance to improve the abilities of elementary school students in Kenari Village, Gayungan District, Surabaya, is motivated by the low ability of students to calculate as indicated by the results of initial observations, namely 65% ​​of students have not been able to complete basic arithmetic operations correctly, as well as low interest in learning mathematics in 60% of students. This condition is influenced by limited learning assistance outside of school and the lack of use of interesting learning methods. This program aims to improve students' ability to calculate, interest in learning, and confidence in solving mathematics problems. The method used is Participatory Action Research (PAR) with the stages of problem identification, action planning, implementation of assistance, observation, and reflection. The assistance model is carried out through a small group learning approach based on educational games and gradual exercises, so that students are more active in understanding basic mathematical concepts. Data collection techniques use observation, numeracy tests, and documentation. The results of the community service program showed that students' numeracy completion rate increased from 35% to 82%, while their interest in learning increased from 40% to 78%, and their self-confidence increased from 45% to 80%. The uniqueness of this program lies in its implementation of participatory, game-based mentoring that actively engages students in the learning process. Therefore, this program is effective in improving elementary school students' numeracy skills and has the potential for sustainable development in Kenari Village.